2018
DOI: 10.1002/mgg3.444
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of HLA‐DQ, susceptibility genotypes for celiac disease, in Brazilian newborns

Abstract: BackgroundThe frequency of HLA‐DQ2 and DQ8 predisposing genotypes for celiac disease (CD) has shown significant variation among different world regions and has not been previously determined among the highly interbred Brazilian population. The aim of this study was to investigate the frequency of these genotypes among Brazilian newborns (NB).MethodsWe typed DQA1*05 ‐ DQB1*02 (DQ2.5) and DQA1*03 ‐ DQB1*03:02 (DQ8) alleles in 329 NB using qPCR technique. Subsequently we confirmed our results by PCR‐SSP using a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 42 publications
(60 reference statements)
1
0
0
Order By: Relevance
“…34 Compared with our study, higher frequencies in the review by Alarida were reported from Mexico (28.3%), Turkey (22%), North India (15.6%) and Iran (12%). 34 Our findings indicate that more than half (51.6%) of the Ethiopian population is carrying any of the DQ2.5, DQ2.2 and DQ8 haplotypes, which was comparable with the Swedish references (55.9%) and other previous studies performed on the general population in Australia (55.9%), 37 Iran (58%), 18 Saudi Arabia (52.7%), 25 but slightly higher than Brazil (43.7%) 38,39 and Denmark (47.7%). 40 Although this study is the largest HLAgenotyped Ethiopian population to date, it is limited by the fact that children included in the present study were enrolled from only one region and therefore may not represent the whole population in Ethiopia.…”
Section: Discussionsupporting
confidence: 89%
“…34 Compared with our study, higher frequencies in the review by Alarida were reported from Mexico (28.3%), Turkey (22%), North India (15.6%) and Iran (12%). 34 Our findings indicate that more than half (51.6%) of the Ethiopian population is carrying any of the DQ2.5, DQ2.2 and DQ8 haplotypes, which was comparable with the Swedish references (55.9%) and other previous studies performed on the general population in Australia (55.9%), 37 Iran (58%), 18 Saudi Arabia (52.7%), 25 but slightly higher than Brazil (43.7%) 38,39 and Denmark (47.7%). 40 Although this study is the largest HLAgenotyped Ethiopian population to date, it is limited by the fact that children included in the present study were enrolled from only one region and therefore may not represent the whole population in Ethiopia.…”
Section: Discussionsupporting
confidence: 89%